TOXIC DIALOG DALAM AL-QUR’AN DI ERA MEDIA SOSIAL - Yulia Hasanah Jefriyanti; Muhammad Alif (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the principles of dialogic ethics in the Qur'an and their relevance to communication practices on social media in the contemporary era. The main focus in-cludes: (1) the principle of information verification (tabayyun) and the prohibition of preju-dice (tajassus); (2) the prohibition of verbal violence in digital spaces, includ-ing ghībah (backbiting), namīmah (slander), and body shaming; (3) the qaulān communication ethics (six types of Qur'anic speech) as a framework for digital interaction; and (4) constructive dialog methods (jadal aḥsan, qaulan layyinan, da‘wah bil ḥikmah) and conflict de-escalation on social media. This research employs a qualitative ap-proach using Structured Thematic Analysis (STA) which adopts Grounded Theory principles, including sensitizing concept, theoretical sampling, open coding, axial coding, selective cod-ing, constant comparative analysis, record, and data saturation. The primary data source is the Qur'anic mushaf, while secondary sources include credible commentaries (al-Misbah, Ibn Kathir, al-Maraghi) and scientific literature. The findings reveal that the Qur'an provides a comprehensive framework for dialogic ethics in the digital era: (1) the obligation of tabayyun as a filter for information before dissemination; (2) the prohibition of various forms of verbal violence such as ghībah, namīmah, tanābudz bil alqāb (calling by bad nick-names), humazah lumazah (scoffer and slanderer), and tajassus; (3) the concept of qaulān consisting of qaulan sadīdan (true speech), qaulan balīghan (effective speech), qaulan layyinan (gentle speech), qaulan karīman (honorable speech), qaulan ma‘rūfan (kind speech), and qaulan maysūran (easy speech) as guidelines for speech quali-ty; and (4) constructive dialog methods including jadal aḥsan (best debate), da‘wah bil ḥikmah (wise invitation), qaulan layyinan, and the principle of repelling evil with good (id-fa‘ billatī hiya aḥsan). This research is expected to contribute to the development of Qur'an-based digital ethics in the context of Islamic da'wah and education in Indonesia.